OPTIMALISASI PENGELOLAAN KEUANGAN DAN PEMASARAN DIGITAL UMKM MELALUI PELATIHAN APLIKASI CATATMAK DAN GOOGLE MAPS - Devita Ayu Kartika; Zaenal Wafa (Jurnal Pengabdian Masyarakat Sabangka, 2026)
This community service activity aims to support digital change in laundry service MSMEs in Jomboran, Sleman, by using the CatatMak application and optimizing Google Maps services.. The challenges faced by MSMEs include unstructured manual financial recording systems and low digital visibility in navigation applications. The method applied in this community service consisted of four stages: observation, outreach, training and mentoring, and evaluation. The results of the activity showed a significant increase in the digital competence of business owners. Based on the evaluation, it was found that skills in inputting transactions and recording financial reports automatically using the CatatMak application increased from 0% to 100%. In the marketing aspect, business owners can independently create business profiles and Google Maps location points to expand market reach. This community service found out that digitalization of financial management and marketing is successful in increasing operational efficiency and competitiveness of MSMEs in the digital era.